2022
DOI: 10.1016/j.landusepol.2021.105967
|View full text |Cite
|
Sign up to set email alerts
|

Land use/cover change analysis in the Mediterranean region: a regional case study of forest evolution in Castelló (Spain) over 50 years

Abstract: The second half of the 20th century has been characterised by the rural abandonment in several regions of the Mediterranean basin. The general collapse of traditional agriculture and livestock activities brought about an intensive migration movement from inland to coastal areas, which produced a massive forest cover increase in abandoned rural areas. This socioeconomic, spatial and environmental change has led to a situation unknown for centuries in the Mediterranean landscapes. As a consequence, large wildfir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…The adoption of digital tools in agriculture as reported by the "Observatorio para la Digitalización del Sector Agroalimentario," underscores the region's dedication to innovation. 1 Now FVMP envisions working with tools 1 As the "Observatorio para la Digitalización del Sector Agroalimentario" reports, adopting digital tools in agriculture underscores the region's dedication to innovation. The widespread implementation of digital technologies in the agriculture, livestock, and agri-food industries is evidence of this.…”
Section: Valencian Fvmp and Un Sdgsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adoption of digital tools in agriculture as reported by the "Observatorio para la Digitalización del Sector Agroalimentario," underscores the region's dedication to innovation. 1 Now FVMP envisions working with tools 1 As the "Observatorio para la Digitalización del Sector Agroalimentario" reports, adopting digital tools in agriculture underscores the region's dedication to innovation. The widespread implementation of digital technologies in the agriculture, livestock, and agri-food industries is evidence of this.…”
Section: Valencian Fvmp and Un Sdgsmentioning
confidence: 99%
“…Land-use shifts: A study covering the province of Castelló in the Valencia region over 50 years showed a substantial reduction in agricultural land use, with a corresponding increase in abandoned agricultural land and the establishment of dense forest areas. This shift indicates a move away from traditional agriculture due to various factors, including climate change [1].…”
mentioning
confidence: 99%
“…The land-use transfer matrix was widely computed to quantify the area conversions among diverse land-use types [42]. To characterize the contributions of impervious surfaces to the dynamics of different forest types in Hangzhou City, the following land-use transfer matrix was calculated using the tabulate area tool in the ArcGIS 10.2 software:…”
Section: Land-use Transfer Matrixmentioning
confidence: 99%
“…Therefore, research has mainly focused on exploring the driving mechanism of the social economy [10][11][12][13]. Studies on LUCC evolution mechanisms largely include long-term historical evolution characteristic analysis [14,15] and future evolution simulation [16][17][18]. Based on quantitative analysis of land-use change rate, dynamic degree, and other indicators [19,20], the focus has been on remote sensing image interpretation and GIS spatial analysis.…”
Section: Introductionmentioning
confidence: 99%